Clinical-epidemiologycal characteric of tick neuroinfections at children - A. P. Pomogaeva; M. O. Karavaeva; O. V. Obidina (Бюллетень сибирской медицины, 2006)
Piculiarities of tick-borne encefalitis and Lyme borreliosis at children in Tomsk region have been stadid from 1990—2004. Characte- ristiks of clinical forms of tick-borne in acute period at 264 children and 224 children Lyme borreliosis in acute period was presented.